2011
DOI: 10.1371/journal.pgen.1002007
|View full text |Cite
|
Sign up to set email alerts
|

The Genome Sequence of the Leaf-Cutter Ant Atta cephalotes Reveals Insights into Its Obligate Symbiotic Lifestyle

Abstract: Leaf-cutter ants are one of the most important herbivorous insects in the Neotropics, harvesting vast quantities of fresh leaf material. The ants use leaves to cultivate a fungus that serves as the colony's primary food source. This obligate ant-fungus mutualism is one of the few occurrences of farming by non-humans and likely facilitated the formation of their massive colonies. Mature leaf-cutter ant colonies contain millions of workers ranging in size from small garden tenders to large soldiers, resulting in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
230
4

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 233 publications
(243 citation statements)
references
References 95 publications
(143 reference statements)
9
230
4
Order By: Relevance
“…1e) Table 7). Ornithine carbamoyl-transferase (EC 2.1.3.3) was not found among any of the five Hymenopteran insects (A. cephalotes, Camponotus floridanus, Harpegnathus saltator, Apis mellifera, Nasonia vitripennis) that were previously analysed 34 , but was also identified in the L. gongylophorus transcriptome. (b) Two genes coding for enzymes mediating aromatic amino acids biosynthesis, chorismate mutase (EC 5.4.99.5) and aminotransferase (EC 2.6.1.1), had alleles that were significantly upregulated in the gongylidia (Supplementary Table 8), indicating that the essential amino acids phenylalanine and tyrosine are produced in high amounts in the gongylidia.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…1e) Table 7). Ornithine carbamoyl-transferase (EC 2.1.3.3) was not found among any of the five Hymenopteran insects (A. cephalotes, Camponotus floridanus, Harpegnathus saltator, Apis mellifera, Nasonia vitripennis) that were previously analysed 34 , but was also identified in the L. gongylophorus transcriptome. (b) Two genes coding for enzymes mediating aromatic amino acids biosynthesis, chorismate mutase (EC 5.4.99.5) and aminotransferase (EC 2.6.1.1), had alleles that were significantly upregulated in the gongylidia (Supplementary Table 8), indicating that the essential amino acids phenylalanine and tyrosine are produced in high amounts in the gongylidia.…”
Section: Discussionmentioning
confidence: 96%
“…The recently sequenced genomes of A. echinatior and A. cephalotes showed that these two leaf-cutting ants lack two essential genes for arginine biosynthesis that three other genome-sequenced ant species with normal hunter-gatherer life styles have retained 33,34 . Both papers hypothesized that the ensuing inability of these ants to synthesize arginine would probably be compensated by metabolic activities of the fungus-garden symbiont.…”
Section: Discussionmentioning
confidence: 99%
“…We annotated CSP genes in seven published ant genomes (C. floridanus, Harpegnathos saltator, S. invicta, L. humile, Pogonomyrmex barbatus, Acromyrmex echinatior and Atta cephalotes) (Bonasio et al, 2010;Nygaard et al, 2011;Suen et al, 2011;Wurm et al, 2011) (Figure 1). The abbreviations used here are, respectively, Cflo, Hsal, Sinv, Lhum, Pbar, Aech and Acep.…”
Section: Csp Gene Identificationmentioning
confidence: 99%
“…Although limited information about sequencing strategies and assemblies is still available, length reads and strategies to orientate adequately the scaffolds and contigs are critical. For the Senegalese sole, as in other de novo eukaryotic genomes published until now, a two-step strategy is being followed: scaffolding using matepair (Illumina Ò ) and long paired-end libraries (454) with insert sizes comprised between 2 kb and 20 kb, followed by massive whole-genome shotgun sequencing (454 and Illumina paired-ends) to be assembled into smaller contigs (Huang et al 2009;Dalloul et al 2010;Li et al 2010;Suen et al 2011;Woycicki et al 2011). However, de novo assembly of large and complex eukaryotic genomes is still challenging due to repetitive DNA and, in fish, by additional whole-genome duplication (WGD) events that occurred in the teleost lineage (3R and 4R in salmonids).…”
Section: De Novo Genome Sequencingmentioning
confidence: 99%